IMPACT OF UREA ON MONOGASTRIC MAMMALIAN SYSTEM: A SHORT TERM STUDY - BHOWAL, SUJIT KUMAR; DASGUPTA, SUBIR CHANDRA; KARMAKAR, SUSANTA ROY; KAR, ARNAB; CHAKRABARTY, EERONDYUTI; GHOSH, MONALISA; DEY, POULAMI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Urea is a naturally occurring end product of amino acid metabolism in mammalian body. It is also a wide spread fertilizer and considered a nontoxic compound. However repeated exposure to urea has been reported to cause damage to vital body organs like liver, kidney etc. Present study was to evaluate the histopathological effects of urea on liver, kidney and testis as well as their correlation with serum biomarkers ALT, AST concentration as well as investigation of sperm head anomaly. For the study a total of 45 Swiss albino mice were taken and divided into 9 groups each consisting of 5 mice. Group I was kept as control group and given only a normal diet. Remaining groups of animals were given different doses of urea i.e. 50% and 75% of LD50 concentrations of urea at different hour intervals i.e. 24, 48, 72, 96 hours. All the animals were kept in standard experimental condition. There was gradual loss of body weight of treated mice with increased dose of urea. The tissue sections revealed histological alteration of the organs in the treatment group mice which may correlate with the increased concentration of serum ALT, AST and sperm head anomaly. The observations of the study also confirmed the toxic effects of the apparently non-toxic compound, urea at high and repeated doses. It is found that the test compound severely damages the histological architecture as well as function of the liver, kidney and testis.